EVALUATION OF CREATININE-MODIFIED CHILD PUGH SCORE FOR PREDICTING SHORT-TERM PROGNOSIS OF PATIENTS WITH DECOMPENSATED CIRRHOSIS OF LIVER AS COMPARE TO ORIGINAL CHILD PUGH SCORE - Samiullah, Shaikh; Qasim, Rahoopoto; Khalid, Shaikh; Hussain, Baloch Ghulam; Mukhtair, Jaffery; Akbar, Yousfani (Journal of Ayub Medical College Abbottabad, 2009)
Background: Original Child-Turcotte-Pugh (CTP) score has traditionally being used as a useful tool to assess prognosis in cirrhotic patients but the serum creatinine level has recently seen as an important predictor of survival in patients with liver cirrhosis. The aim of this study was to compare the accuracy of CP and modified CP score for predicting in hospital survival as well as cirrhosis related complications such as encephalopathy, haematemesis and ascites in patients with decompensated cirrhosis. It was Descriptive case series. The study was conducted at Department of Medicine, Liaquat University of Medical & Health Sciences Jamshoro from October 2005 to July 2007. Methods: This study included 222 patients with decompensated cirrhosis diagnosed either clinically or radio-logically were followed-up during hospital stay. Patient’s demographic data was enrolled in well designed proforma which included enquiry regarding cirrhosis related complications. Patients were classified according to original CP classification into A, B and C and modified Child Pugh scores estimated by adding 0, 2 and 4 points with serum creatinine <1.3 mg/dL,1.3-1.8 and >1.8 mg/dl respectively to the original score using creatinine levels as a sixth categorical variable were evaluated. Simple t-test and Chi-square test were done for continuous and categorical data. Original CP and creatinine modified CP was compared by the ROC curve. p<0.05 was considered significant. Results: In this study 222 cirrhotic patients constituting 144 (65% male and 78 (35%) female. The mean age of the patients were 46.8±12.8 and mean serum creatinine 1.41±0.55 mg/dl. In Original Child-pugh classification 9, 82, 131 out of 222 were in grade A, B and C respectively whereas in creatinine-modified child-pugh classification 7, 28 and 187 patients were in grade A, B and C respectively. For cirrhosis related complications creatinine modified child Pugh has a better predictive value for encephalopathy (p=0.03) as compared to original child Pugh (p=0.42) whereas for haematemesis (p=0.001) and grades of ascites (p=0.003) creatinine modified CP was marginally better than original CP (p=0.004) and (p=0.007) respectively. Predicting the in hospital death and duration of hospitalization as outcome creatinine modified CP (p=0.001) as compared to original CP (p=0.004). ROC (receiver-operating characteristic) curve the creatinine-modified CTP score showed a marginal, better prognostic accuracy as compared with the CTP score (CTP vs creatinine-modified CTP, c-index and 95% CI=0.654 (0.578-0.731), vs 0.642 (0.562-0.722), p=0.001). Conclusion: Inclusion of serum creatinine can improve the prognostic value of Child-Pugh classification particularly class B in which the serum creatinine play a major role in properly predicted the survival as well as cirrhosis related complications. Keywords: child-pugh, cirrhosis of liver, serum creatinine, encephalopathy.